Effects of key parameters on pulsed field ablation of atrial fibrillation: potato experiments - Yunhao Li; Yunhao Li; Fengqi Xuan; Daoyang Zhang; Daoyang Zhang; Mingyu Sun; Mingyu Sun; Ping Zhang; Qi Zhang; Jie Zhang; Yaling Han; Yaling Han; et al. (Frontiers in Cardiovascular Medicine)
AimsThe study aims to investigate the impact of key parameters of pulsed field ablation (PFA) on lesion depth, including voltage (V), pulse width (PW), number of pulses (P), and ablation number (N), using potato models.MethodsPotatoes are utilized as a display of the irreversible electroporation lesion. The key ablation parameters were varied systematically to explore its influences on lesion depths.Results and conclusionThe key ablation parameters have varying degrees of influence on lesion depths, following the order of PW>V; V>P; PW>P; N>P. Lesion depths increased with higher values of V and P. However, when the total number of pulses reached 9,600, there was no significant increase in injury depth.